The Six-Day War - Broyles, Matthew (New York The Rosen Publishing Group, INC, 2004)
Examines the history behind the 1967 war between Israel and its surrounding Arab neighbors, Egypt, Syria, and Jordan, plus biographical notes on important figures and a look at the effects of this war.
The Arabs and the Jews -- Countdown to war -- Israel faces war, and the world -- War begins -- Jerusalem and the Golan Heights -- Aftermath.
Includes bibliography references and Index
Keywords: Israel-Arab War -- Juvenile literature -- 1967; Arab-Israeli conflict -- Juvenile literature